Failure behaviors of terraced loess slope induced by intermittent heavy rainfall: centrifuge model test and numerical simulation - Jia, Jun; Dong, Ying; Guo, Xiaopeng; Liu, Gang; Gu, Qi (Frontiers in Earth Science, 2025)
In the Loess Plateau, extreme rainfall events frequently trigger instability in loess cut-slopes with weak structures. Nevertheless, the deformation and failure characteristics of terraced loess cut-slopes with cracks under extreme rainfalls remain insufficiently studied and poorly understood. This paper presents the centrifuge model test on the deformation and failure behaviors of the terraced loess slope under intermittent rainfall conditions. The terraced loess slope, featuring two berms and a prefabricated crack along its crest, was initially subjected to loading up to 50 g before undergoing intermittent rainfalls. The deformation and failure processes of the slope were monitored using laser displacement meters and a high-resolution digital camera mounted. Furthermore, comprehensive monitoring and analysis were conducted on the slope’s mechanical-hydrological responses, including variations of earth pressure and volumetric water content. Finally, numerical modellings using the hybrid finite-discrete element method were performed to extensively explore the effect of crack on the physical and mechanical responses to rainfall. The experimental and numerical results indicate that the slope failure process exhibits distinct evolutionary characteristics under rainfall conditions. Rainfall infiltration triggers the phased responses. Early-stage rainfall causes upper slope erosion with subsequent sediment deposition in lower sections. As rainfall continues, erosion focus shifts downward while upper slope erosion persists. Progressive infiltration leads to soil structure weakening, evidenced by reduced stress concentration and inward migration of the maximum shear stress zone. This process is accelerated by pre-existing cracks that establish preferential infiltration pathways. Notably, while increasing rainfall intensity and frequency exacerbate erosion (manifested as gully widening and deepening) and earth pressure fluctuations, the spatial distribution of erosion remains constrained by preformed cracks, particularly in controlling gully initiation points at the slope top. The findings can provide a basis for assessing the stability of fissured loess slopes and forecasting the potential for rainfall-triggered loess landslides.